Bacterial polysaccharide synthesis and export. (October 2016) - Woodward, Laura; Naismith, James H
Highlights: In bacteria carbohydrate polymers undergo a journey from inside to outside the cell. Many membrane proteins are key to the synthesis and translocation of the polymers. Structural information on the process is becoming increasingly rich. Abstract : All domains of life make carbohydrate polymers and by anchoring them to lipid molecules they can decorate the outside of the cell. Polysaccharides are linked to proteins by glycosylation, a process found in both bacteria and in higher organisms. Bacteria do have other distinct uses for carbohydrate polymers; in gram-negative bacteria glycolipids form the outer leaflet of the outer membrane and in many pathogens (both gram-positive and gram-negative) sugar polymers are used to build a capsule or are secreted into the environment. There are parallels, but of course differences, in the biosynthesis of glycolipids between prokaryotes and eukaryotes, which occur at the membrane. The translocation of large sugar polymers across the outer membrane is unique to gram-negative bacteria. Recent progress in the molecular understanding of both the biosynthesis at the inner membrane and the translocation across the outer membrane are reviewed here.